The behaviour of the heart rate of the professional football player in competition. Is possible to explain it from the context of the game situation? - O. García; T. Ardá; A. Rial; E. Domínguez (Asociación Española de Ciencias del Deporte, 2010)
The aim of the study is of going more deeply into the knowledge of the behaviour of the HR of the professional football players into competition, identifying the most relevant criteria that define the context of the game situation where the professional players presents a marked increase in his values of HR in competition, elaborating a distinctive profile of the type of game situation associated with a high physiological load. To reach the mentioned aims it has resorted to a mixed methodology, in which the utilization of the methodology observational in complemented with a selective methodology. For the analysis of information there were retained a whole of 153 cases, correspondents to a whole of 6 professional players belonging to the first team of the R.C. Celta de Vigo, classified to dispute the Champions League in the season 2003/04. The results seem to indicate that they are three criteria that they allow arrange of a model with a high explanatory capacity of more than 80% of the variance of the behaviour of the HR, measured by the marked increases and the decreases in the values: centre of game, role and opposition, specially the first of them turns out to be key at the moment of being able to explain or predict it. Key Words: soccer, heart rate, game situation, centre of game.